Reduce, reuse, sustainable recycle and recovery technique in construction waste management - Mustaffa Kamal, Mohd Firdaus (2009)
Construction industry consume substantial amount of raw materials in the process and the output is obviously the product and most importantly the waste material. Other than that, construction industry is well known as one of the worst environmental polluters. This study is to determine the use of waste minimization technique in creating sustainable waste management in order to identify the technique which has the most capabilities to reduce waste on-site. The objective is to assess the waste minimization techniques taken from the 4R concept which is reduce, reuse, recycle and recovery technique in minimizing the waste in construction waste management. Questionnaire has been distributed randomly across the district of Johor Bahru, and the data has been analyzed using Statistical Packages for Social Science (SPSS) software to determine whether the output meet its original objective. The most used waste minimization technique found in 4R concept would be the waste reduction. This shows that local construction industry has the awareness to plan out the waste management planning but the implementation is still far from satisfying. This is has been proven with the result of second objective which shows that none of the techniques tested in the 4R concept gave a significant relationship in minimizing the waste produced on site. However among four techniques tested for this research, waste recycle gave significant difference. This shows that physical profit gave reasoning for the construction practitioners to adapt to this technique because the nature of the industry which is profit making.